Associations of intimate partner violence and reproductive coercion with contraceptive use in Uttar Pradesh, India: How associations differ across contraceptive methods - Tomar, Shweta; Dehingia, Nabamallika; Dey, Arnab K.; Chandurkar, Dharmendra; Raj, Anita; Silverman, Jay G. (PloS one, 2020)
Intimate partner violence (IPV) and reproductive coercion (RC)-largely in the form of pressuring pregnancy-appear to contribute to low use of contraceptives in India; however, little is known about the extent to which these experiences differentially affect use of specific contraceptive methods. The current study assessed the association of IPV and RC with specific contraceptive methods (Intrauterine Devices [IUDs], pills, condoms) among a large population-based sample of currently married women (15-49 years, n = 1424) living in Uttar Pradesh. Outcomes variables included past year modern contraceptive use and type of contraceptive used. Primary independent variables included lifetime experience of RC by current husband or in-laws, and lifetime experiences of physical IPV and sexual IPV by current husband. Multivariate logistic regression models were developed to determine the effect of each form of abuse on women's contraceptive use. Approximately 1 in 7 women (15.1%) reported experiencing RC from their current husband or in-laws ever in their lifetime, 37.4% reported experience of physical IPV and 8.3% reported experience of sexual IPV by their current husband ever in their lifetime. Women experiencing RC were less likely to use any modern contraceptive (AOR: 0.18; 95% CI: 0.9-0.36). Such women also less likely to report pill and condom use but were more likely to report IUD use. Neither form of IPV were associated with either overall or method specific contraceptive use. Study findings highlight that RC may influence contraceptive use differently based on type of contraceptive, with less detectable, female-controlled contraceptives such as IUD preferred in the context of women facing RC. Unfortunately, IUD uptake remains low in India. Increased access and support for use, particularly for women contending with RC, may be important for improving women's control over contraceptive use and reducing unintended pregnancy.